KERAGAAN LEMBAGA KEUANGAN DI KECAMATAN PANGALENGAN, KABUPATEN BANDUNG - Annida Aisah; Eliana Wulandari (Universitas Galuh Ciamis, 2020)
Pangalengan Sub District is one of the largest potato production centers in West Java. Lack of capital of farmers, uncertain yields and very high production input prices cause farmers need to access credit from financial institutions, both bank and non-bank financial institutions. Agriculture sector is a high-risk sector, financial institutions especially banks are less interested in financing the agricultural business. This research applies descriptive analysis using primary and secondary data. The results showed that the difficulty of farmers' access to financial institutions was due to requirements that could not be fulfilled by some farmers in Pangalengan Sub District.